CBT-based psychological rehabilitation program for oncological patients - A. Juhász; Z. Horváth; T. Szekeres; G. Vizin (European Psychiatry, 2022)
Introduction Although the survival rate of cancer patients show an increasing trend due to more effective treatments plans, cancer mortality rates are still the highest in Hungary among EU countries. From a psychological perspective, undiagnosed psychological disorders, insufficient treatment, and also poor adherence to treatment are recognized factors behind the saddening mortality data.